Perceiving Positive Facial Expression Can Relieve Depressive Moods: The Effect of Emotional Contagion on Mood in People With Subthreshold Depression - Yamashita, Yuko; Yamamoto, Tetsuya (Frontiers in Psychology, 2021)
Emotional contagion is a phenomenon by which an individual’s emotions directly trigger similar emotions in others. We explored the possibility that perceiving others’ emotional facial expressions affect mood in people with subthreshold depression (sD). Around 49 participants were divided into the following four groups: participants with no depression (ND) presented with happy faces; ND participants presented with sad faces; sD participants presented with happy faces; and sD participants presented with sad faces. Participants were asked to answer an inventory about their emotional states before and after viewing the emotional faces to investigate the influence of emotional contagion on their mood. Regardless of depressive tendency, the groups presented with happy faces exhibited a slight increase in the happy mood score and a decrease in the sad mood score. The groups presented with sad faces exhibited an increased sad mood score and a decreased happy mood score. These results demonstrate that emotional contagion affects the mood in people with sD, as well as in individuals with ND. These results indicate that emotional contagion could relieve depressive moods in people with sD. It demonstrates the importance of the emotional facial expressions of those around people with sD such as family and friends from the viewpoint of emotional contagion.